THE POLYTHEISTIC PSYCHE: RE-IMAGINING SOUL AND SELF IN JAME’S HILLMAN’S ARCHETYPAL PSYCHOLOGY - Джон, Кинг (SWorldJournal, 2021)
This article examines the notion of psychological polytheism in the context of Jungian depth psychology. The author focuses on the concept of the “polytheistic psyche” which American psychologist and philosopher James Hillman, founder of the post-Jungian